From England to Bohemia: heresy and communication in the later Middle Ages - Van Dussen, Michael (Cambridge studies in medieval literature, 2012)
"This is the first book-length study of the influential cultural and religious exchanges which took place between England and Bohemia following Richard II's marriage to Anne of Bohemia in 1382. The ensuing growth in communication between the two kingdoms initially enabled new ideas of religion to flourish in both countries but eventually led the English authorities to suppress heresy. This exciting project has been made possible by the discovery of new manuscripts after the opening up of Czech archives over the past twenty years. It is the only study to analyze the Lollard-Hussite exchange with an eye to the new opportunities for international travel and correspondence to which the Great Schism gave rise, and examines how the use of propaganda and The Council of Constance brought an end to this communication by securing the condemnation of heretics such as John Wyclif"--